2016
DOI: 10.1111/pde.12806
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpigmented Plaques of the Alar Crease: An Unusual Presentation of Acanthosis Nigricans

Abstract: Although acanthosis nigricans of the posterior neck and intertriginous areas is common, acanthosis nigricans of the supra-alar creases is rare. We present the case of an obese 16-year-old African American boy with hyperpigmented plaques along the supra-alar creases of his nose. Clinicians should be aware of this rare manifestation, because newly diagnosed acanthosis nigricans should prompt examination for insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…While various pediatric nasal creases and lines have been reported, they have only recently been identified in the literature as uncommon presentations of AN . Furthermore, we did not find any previously reported association of transverse nasal AN with allergic saluting or allergic rhinitis in a pediatric patient during our review of the literature.…”
Section: Case Discussioncontrasting
confidence: 53%
“…While various pediatric nasal creases and lines have been reported, they have only recently been identified in the literature as uncommon presentations of AN . Furthermore, we did not find any previously reported association of transverse nasal AN with allergic saluting or allergic rhinitis in a pediatric patient during our review of the literature.…”
Section: Case Discussioncontrasting
confidence: 53%
“…In contrast, the face, eyelids, supra-alar nasal creases, inner thigh, antecubital fossa, popliteal fossa, umbilicus, palms, soles, knuckles (Figure 5), nipples, and areolas are less frequently involved areas 25,28. The neck and axillae are frequently involved and are sites that are more socially acceptable than others for screening.…”
Section: Current Knowledge On Anmentioning
confidence: 99%
“…A rare cause of acanthosis nigricans that is often overlooked is Lelis syndrome (LS), a unique clinical syndrome characterized by ectodermal dysplasia and acanthosis nigricans . Some authors have suggested that LS occurs secondary to mutations in the EDA gene.…”
mentioning
confidence: 99%